Evidence based postoperative treatment of distal radius fractures following internal locking plate fixation - Klein, S M; Prantl, L; Koller, M; Vykoukal, J; Dolderer, J H; Graf, S; Nerlich, M; Loibl, M; Geis, S (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2015)
Originally, the treatment method of choice for distal radial fractures (DRF) has been a non-operative approach with six to eight weeks of plaster casting. The introduction of volar locking plate systems at the beginning of the 21 st century has pushed trends towards open reduction and internal fixation (ORIF). While the introduction of fixed angle locking plates together with the increasing knowledge on wrist function and related variable outcomes has led to consensus that operative fixation in instable DRF is the treatment method of choice, there is no agreement on a postoperative care of these injuries. The authors will discuss the available evidence for current concepts of postoperative treatment of DRFs following fixed angle fixation under socioeconomical, biomechanical and burden of disease aspects. Further, relevant randomized controlled trials are evaluated with regard to applied postoperative treatment regimes and related risks for complications.
Keywords: kostní destičky; medicína založená na důkazech; socioekonomické faktory; Bone Plates; Wrist Injuries; fraktury vřetenní kosti; Radius Fractures; Evidence-Based Medicine; Fracture Fixation, Internal; Humans; časné pohybování; poranění zápěstí; pooperační péče; vnitřní fixace fraktury; Postoperative Care; lidé; Early Ambulation; Socioeconomic Factors